Human Resource Development Management in Creating a New Workforce Through the Internship Program to Japan at the Department of Manpower, East Lombok Regency - Masbullah, Masbullah; Abdul Ghofar (Sean Institute, 2025)
The problems of unemployment and the low competitiveness of the workforce remain major challenges in labor development in East Lombok Regency. A strategic effort undertaken to address these issues is the internship program to Japan as a means of developing human resources (HR) to create a new, competent workforce. This study aims to examine the management of HR development in the implementation of the internship program to Japan by the Department of Manpower of East Lombok Regency. The research method employed is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observations, document analysis, and literature review, and were analyzed using the Miles and Huberman model. The research focuses on two main aspects: the recruitment and selection process of participants, as well as the implementation of HR development, which includes planning, execution, and evaluation. The findings reveal that the internship program to Japan is well-structured and effectively implemented, supported by strong leadership, competent human resources, internal communication, and external support from IM Japan and national regulations. Nevertheless, several challenges persist, including limited budget, training facilities, trainers, and uneven community support. The study recommends institutional strengthening, increased funding and infrastructure, inter-agency collaboration, community involvement, and the development of a digital monitoring system to ensure program sustainability.